The contestation of code. - Berry, David M. (Critical Discourse Studies, 2004)
This paper uses discourse analysis to examine the free/libre and open source movements. It analyses how they fix elements within the order of discourse of computer code production. It attempts to uncover the key signifiers in their discourses and trace linkages between the sedimented discourses of wider society. Using discourse theory and critical discourse analysis, the theoretical foundations underpinning each of the movements are critically examined and the effect on the wider developer and Internet community is discussed. Additionally, this paper seeks to recommend discursive strategies that could be employed to avoid the threat of colonization by neoliberal discourse and the consequent challenge this has for the ideas of freedom, liberty and community within the developer communities' own discourses.